Rapid Blood Clot Removal via Remote Delamination and Magnetization of Clot Debris - Qinglong Wang; Ben Wang; Kai Fung Chan; Xin Song; Qianqian Wang; Fengtong Ji; Lin Su; Bonaventure Yiu Ming Ip; Ho Ko; Philip Wai Yan Chiu; Thomas Wai Hong Leung; Li Zhang (Advanced Science)
Abstract Micro/nano‐scale robotic devices are emerging as a cutting‐edge approach for precision intravascular therapies, offering the potential for highly targeted drug delivery. While employing micro/nanorobotics for stroke treatment is a promising strategy due to its ability to localize therapy and minimize drug dosage, current methods require prolonged treatment durations, increasing the risk of nerve tissue necrosis from extended hypoxia. Here a programmable colloidal microswarm capable of rapidly detaching blood clots from the vessel wall is developed, enabling swift recanalization without the need for complete clot degradation. More importantly, the detached clot debris, despite their random shapes, functions as magnetic “debris‐robots” and can be efficiently propelled through helical swimming within flowing vessels, followed by retrieval using catheter suction. The entire process—including catheter delivery, controlled locomotion, clot detachment, and retrieval—can be completed in approximately half an hour, significantly saving time compared to the critical “Golden 6 hours” window for stroke treatment. This retrieval procedure greatly minimizes nanoparticle exposure in the bloodstream and lowers the risk of secondary clotting in distal vessels, marking a significant advancement in robotic‐assisted thrombolysis.